Progressive Thoracolumbar Tuberculosis in a Young Male: Diagnostic, Therapeutic, and Surgical Insights - Dana-Georgiana Nedelea; Diana Elena Vulpe; George Viscopoleanu; Alexandru Constantin Radulescu; Alexandra Ana Mihailescu; Sebastian Gradinaru; Mihnea Orghidan; Cristian Scheau; Romica Cergan; Serban Dragosloveanu (MDPI AG, 2024)
Objective: We present the case of a 26-year-old male with severe spinal tuberculosis of the thoracolumbar region. The patient suffered from worsening back pain over five years, initially responding to over-the-counter analgesics. Despite being proposed surgery in 2019, the patient refused the intervention and subsequently experienced significant disease progression. Methods: Upon re-presentation in 2022, mild involvement of the T12-L1 vertebrae was recorded by imaging, leading to a percutaneous needle biopsy which confirmed tuberculosis. Despite undergoing anti-tuberculous therapy for one year, the follow-up in 2024 revealed extensive infection from T10 to S1, with large psoas abscesses and a pseudo-tumoral mass of the right thigh. The patient was ultimately submitted to a two-stage surgical intervention: anterior resection and reconstruction of T11-L1 with an expandable cage, followed by posterior stabilization from T8-S1. Results: Postoperative recovery was uneventful, with significant pain relief and no neurological deficits. The patient was discharged on a continued anti-tuberculous regimen and remains under close surveillance. Conclusions: This paper presents details on the challenges of diagnosis and management of severe spinal tuberculosis, with emphasis on the importance of timely intervention and multidisciplinary care.